Dietary intake of n-3 PUFAs modifies the absorption, distribution and bioavailability of fatty acids in the mouse gastrointestinal tract. Issue 1 (December 2017) - Yang, Qin; Wang, Shunhe; Ji, Yunqi; Chen, Haiqin; Zhang, Hao; Chen, Wei; Gu, Zhennan; Chen, Yong
Abstract Background Dietary polyunsaturated fatty acids (PUFAs), especially n-3 PUFAs, are important for human health. The intestinal tract, a location that is heavily colonized by microorganisms, is the main organ for absorbing fatty acids. Methods The purpose of this study was to analyze the effects of dietary n-3 and n-6 PUFAs on the distribution of different types of fatty acids and their bioavailability along the gut. Mice were fed for a week with experimental diets containing high n-3 or high n-6 fatty acid levels. Blood was collected at different time points, and after 7 days the mice were euthanized and their digestive tract was divided into 17 segments for fatty acids analyses. Results We found that supplementing n-3 fatty acids significantly changed the ratio of n-6/n-3 PUFAs, increased the bioavailability of n-3 PUFAs, and altered fatty acid distribution. In addition, in the n-3 diet group, the absorption of saturated fatty acids (SFAs) along the gut was found to be inhibited, which was confirmed by feeding the mice with a diet containing deuterium-labeled palmitic acid and stearic acid. Conclusion These results show that a diet rich in n-3 PUFAs can significantly modify the distribution and bioavailability of fatty acids, and particularly, may block the absorption of SFAs in the mouse gastrointestinal (GI) tract.